2017
DOI: 10.1007/s11325-017-1533-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between obstructive sleep apnea severity and endoscopically proven gastroesophageal reflux disease

Abstract: Endoscopically proven GERD was associated with more severe OSA. GERD symptoms were also associated with deteriorated sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…The etiology of symptoms may be multifactorial for patients with concomitant LPR and obstructive sleep apnea syndrome, based on recent data that supported a strong association between obstructive sleep apnea syndrome severity and reflux symptoms. 28…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of symptoms may be multifactorial for patients with concomitant LPR and obstructive sleep apnea syndrome, based on recent data that supported a strong association between obstructive sleep apnea syndrome severity and reflux symptoms. 28…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al ascertained that esophagogastroduodenoscopy-proven GERD was significantly associated with OSA, which substantiates our study’s results. A recurrent upper airway narrowing among OSA patients during sleep could result in negative intra-thoracic pressure during inspiration [32]. The increased intrathoracic pressure might facilitate acid reflux into the esophagus, which finally leads to GERD [32].…”
Section: Discussionmentioning
confidence: 99%
“…A recurrent upper airway narrowing among OSA patients during sleep could result in negative intra-thoracic pressure during inspiration [32]. The increased intrathoracic pressure might facilitate acid reflux into the esophagus, which finally leads to GERD [32]. GERD could deteriorate OSA by aggravating the airway resistance by causing posterior laryngitis [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, more studies are using polysomnography to document apnea index and 24-h pH monitoring to document the acid reflux and the prevalence of GERD in OSAHS patients. Kim et al [ 10 ] found GERD was associated with more severe OSAHS and GERD symptoms were also associated with deteriorated sleep quality. However, this pathophysiological mechanism has been questioned in some studies as they find negative results.…”
Section: Introductionmentioning
confidence: 99%